Classification of forced contacts in adolescents prone to addictive behavior who are in social rehabilitation - O.I. Mironova; A.A. Golenkov (Психология и право)
Context and Relevance. Within the framework of the concept of pedagogical communication by A.A. Leontjev (Leontjev, 2005) and the socio-psychological concept of forced contacts by O.I. Mironova (Mironova, 2014), the phenomenon of forced contact among adolescents prone to addictive behavior and undergoing social rehabilitation is considered as one of the key concepts of a specialized program for providing assistance to minors. Objective. To develop a classification of forced contacts among adolescents who are prone to addictive behavior and are undergoing social rehabilitation. Results. Various types of forced contacts in adolescents are proposed and characterized. Conclusions. The grounds for classifying forced contacts are highlighted: the motivating factor, the forms of interaction, the number of participants in the interaction, the method of communication, the duration of contact, emotional response, subjective assessment of the significant other, areas of the activity, the time of onset of affect in a teenager.